Development of Healthy Diet Guidebook to Promote Healthy Lifestyle - Tukiran, Nor Anis Intan Aqiah; Nor Aziah Ahmad; Adibah Aishah Md Sahak; Abdul Wafi Abdul Rahman; Mustika Amira binti Mustafa Halim; Lisa Mariam Syawal Ismail (Research and Innovation in Technical and Vocational Education and Training, 2021)
This decade, the community has been experiencing a revolution in which the problem of malnutrition has been turned into a society that is experiencing food shortages leading to serious health problems. Adolescents also experience this problem especially for adolescents involved in food production such as catering. This is also due to the lack of knowledge about nutrition in the community especially among adolescents. Lack of exposure to nutritional care will take this problem further. The purpose of developing of the guidebook healthy diet style is to provide guidance on maintaining a healthy diet and maintaining proper nutrition in daily life. Individuals also have the opportunity to come up with a daily diet plan. The methodology chosen in the development of this guide book is to use the ADDIE model. The guide book developed has been certified by 5 experts from the faculty of the Faculty of Technical and Vocational Education and evaluated using the questionnaire form. Data processing is done using Microsoft excel software by assessing the frequency and percentage of the content list, presentation, design and clarity of the guide book. The percentage obtained was 98%. This indicates that the guide book developed is suitable for use as a guide. The results of the development of the guidebook healthy diet style are expected to increase knowledge and provide guidance to the community on healthy diet. Keyword : Development, Guide, ADDIE, healthy